2022
DOI: 10.1002/admi.202201935
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Performance of Fiber‐Reinforced Polymer Composites Using Carbon Nanotubes as an Effective Nano‐Phase Reinforcement

Abstract: Carbon nanotubes (CNTs) are an economical and multi‐functional nanofiller that can further elevate the versatile performance of fiber‐reinforced polymer (FRP). The past two decades have seen significant progress in the design, fabrication, and characterization of CNTs modified FRPs (CNT‐FRPs). The introduction of CNTs has been proven to enhance the key mechanical properties of CNT‐FRPs and endow the composite with additional functional properties. In this review, the fabrication routes of CNT incorporation int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 167 publications
(276 reference statements)
1
6
0
Order By: Relevance
“…[35] observed that carbon nanotubes exhibit robust adhesion to fiber surfaces and can penetrate the interstitial spaces between the fibrils within the fibers. Additionally, the interaction between fibers and nanotubes is reinforced by Van der Waals forces and the expansion effect, as highlighted in previous research [34]. It can be seen that the (curauá + MWCNT) + resin composites presented an increase of approx.…”
Section: Mechanical Propertiessupporting
confidence: 63%
“…[35] observed that carbon nanotubes exhibit robust adhesion to fiber surfaces and can penetrate the interstitial spaces between the fibrils within the fibers. Additionally, the interaction between fibers and nanotubes is reinforced by Van der Waals forces and the expansion effect, as highlighted in previous research [34]. It can be seen that the (curauá + MWCNT) + resin composites presented an increase of approx.…”
Section: Mechanical Propertiessupporting
confidence: 63%
“…CNTs have excellent mechanical properties. Tensile strength reaching values between 25-66 GPa [23,24] and a Young's modulus greater than 1 TPa [25,26]. The excellent mechanical properties of the carbon nanofiller are responsible for the increased strength of PLA composites with carbon nanotubes [27].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, nanoclay is commonly used as a filler in polymer composite materials 19 and can improve the mechanical properties of polymers with only a small amount of addition. 20 Recently, various treatment techniques have been explored, such as improving the filtration rate of bentonite suspensions 21 and its effect as a coagulant. 22 Nanoclays such as montmorillonite and bentonite are typically hydrophilic, hence surface treatment 23 is required for the material to not spontaneously wet if placed at the air/water interface.…”
Section: Introductionmentioning
confidence: 99%
“…However, many natural clays have high aspect ratio 18 with a thickness of 1 nm and a width reaching the micron level, enable wide areal coverage with a small amount when used as a thin film. Additionally, nanoclay is commonly used as a filler in polymer composite materials 19 and can improve the mechanical properties of polymers with only a small amount of addition 20 . Recently, various treatment techniques have been explored, such as improving the filtration rate of bentonite suspensions 21 and its effect as a coagulant 22 …”
Section: Introductionmentioning
confidence: 99%